Merancang Mesin Kemas Untuk Makanan Ringan - Aziz, Ozi Abdul (JTTM : Jurnal Terapan Teknik Mesin, 2020)
Background Good packaging is expected to be able to attract the tastes of consumers, so that it can be used as a promotional tool that is also expected to boost sales volume. Aim The purpose of this design is to look for good packaging results and increase production results. Method Data taken using the VID2221 method and the VDI2225 method. Result Making this machine is to create a packaging machine that is simple and inexpensive to be used by snack entrepreneurs in the home industry, as well as large industries. Conclusion one work or processing one package, it takes 0.679 seconds, so in one minute it can produce a maximum of 88 packages and the compressor power used to run the machine so that it can run with continue is using a 4.5 Pk compressor.